TA’YIN; PENENTUAN BAGIAN AHLI WARIS SEBELUM PEMBAGIAN WARISAN - Raja Ritonga (IAIN BONE, 2021)
AbstractThis study discusses the problem of the process of determining the share of heirs and the process of inheritance distribution in Islamic inheritance law. This research is a library research, with a qualitative approach. The results in this study are that the ta'yin (determination) of the share of each heir in Islam is obligated to use the provisions of the Qur'an and Hadith. Because the determination of inheritance with a family and customary system can open a gap for jealousy and conflict among heirs, because there is no standard guide in its application. So that the ta'yin process is carried out so that each heir knows what part he will receive. Furthermore, if all the members of heir agreed and have willing to do the sharing inheritance by kinship or tradition, then, this process is valid and do not conflict with Islamic’s law. As a conclusion, ta’yin heir members divisions have to do in every sharing inheritance. Whereas the process of sharing inheritance is given appropriate to the agreement reached by the heirs. Keywords: Determining of Division; Heir Members; Sharing Inheritance; Ta’yin.AbstrakPenelitian ini membahas masalah proses penentuan bagian ahli waris dan proses pembagian warisan dalam hukum waris Islam. Penelitian ini merupakan library research, dengan pendekatan kualitatif. Hasil dalam penelitian ini yaitu bahwa ta’yin (penentuan) bagian masing-masing ahli waris dalam Islam wajib hukumnya menggunakan ketentuan al-Qur’an dan Hadis. Karena penentuan warisan dengan sistem kekeluargaan dan adat dapat membuka celah kecemburuan dan konflik sesama ahli waris, sebab tidak adanya panduan baku dalam penerapannya. Sehingga proses ta’yin dilakukan agar setiap ahli waris mengatahui bagian yang akan diterimanya. Selanjutnya, apabila semua ahli waris bersepakat dan sama-sama ridha untuk melakukan pembagian secara kekeluargaan atau adat, maka proses ini adalah sah dan tidak menyalahi hukum Islam.Kata Kunci: Penentuan Bagian; Ahli Waris; Pembagian Warisan; Ta’yin.